1997
DOI: 10.1159/000456974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Casein and Soy Protein Isolate on Vitamin B(6) Nutritional Status in Rats

Abstract: Two experiments were conducted to test the effect of casein and soy protein isolate (SPI) on the nutritional status of vitamin B(6) in rats. Adult Long-Evans rats were fed with a casein or SPI diet at a 40% protein level with (control) or without (B(6)-deficient) 7 mg of pyridoxine/kg diet. Vitamin-B6-deficient rats were depleted of B(6) with (experiment 1) or without (experiment 2) deoxypyridoxine. In experiment 1, each rat was loaded with 150 mg of DL-tryptophan after 5 weeks of pair feeding. The rats on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, the pyridoxine status is likely to be low at weaning. Moreover, as in rats (Lu & Huang, 1997) and in humans subjects (Bender, 1999), the reduced quality and increased quantity of protein in the post-weaning feed, as opposed to sows' milk, would further increase the B 6 needs, because of an increased interconversion and oxidation of amino acids; those metabolic pathways are, in many cases, pyridoxal phosphate dependent. In fact, in weaned piglets, it was suggested that the dietary levels of B 6 which maximise growth performance would be two to five times higher than for the growing±finishing pigs (Adams et al 1967;Ko Èsters & Kirchgessner, 1976;Bretzinger, 1991;National Research Council, 1998).…”
Section: Vitamin B 6 : Pyridoxal: Glucose: Tryptophan: Weanling Pigletsmentioning
confidence: 99%
“…Therefore, the pyridoxine status is likely to be low at weaning. Moreover, as in rats (Lu & Huang, 1997) and in humans subjects (Bender, 1999), the reduced quality and increased quantity of protein in the post-weaning feed, as opposed to sows' milk, would further increase the B 6 needs, because of an increased interconversion and oxidation of amino acids; those metabolic pathways are, in many cases, pyridoxal phosphate dependent. In fact, in weaned piglets, it was suggested that the dietary levels of B 6 which maximise growth performance would be two to five times higher than for the growing±finishing pigs (Adams et al 1967;Ko Èsters & Kirchgessner, 1976;Bretzinger, 1991;National Research Council, 1998).…”
Section: Vitamin B 6 : Pyridoxal: Glucose: Tryptophan: Weanling Pigletsmentioning
confidence: 99%
“…In fact, sow milk is a poor dietary source of B 6 (Benedikt et al 1996), approximately 0•4 mg/ml, which is believed to cover less than half the amount required to sustain the piglet growth rate (Coburn, 1994). Moreover, as in rats (Lu & Huang, 1997) and humans (Bender, 1999), the reduced quality and increased quantity of protein in the postweaning feed, as opposed to dam's milk, would further increase the B 6 needs, because of an increased interconversion and oxidation of amino acids; those metabolic pathways are, in many cases, B 6 -dependent. The interaction between metabolic utilization of B 6 and protein accretion or growth rate (Matte et al 1997(Matte et al , 2001) has been also linked to its action on insulin, a key hormone for protein synthesis and deposition (Davis et al 1996).…”
mentioning
confidence: 99%
“…In a rat study, after being fed the same vitamin B-6 intake in a B-6 deficient diet for 5 wk and given a tryptophan load, rats fed soy protein isolate excreted twice the amount of urinary xanthurenic acid in 24 h compared with rats fed casein. Moreover, lower erythrocyte aminotransferase activity also indicated reduced vitamin B-6 status in the rats fed soy protein (Lu and Huang 1997). The results suggest that the source of dietary protein significantly affected the B-6 status in these rats.…”
Section: Dietary Factors Affecting Statusmentioning
confidence: 75%
“…There has been limited information regarding the PNG content in soymilk. Moreover, a study in rats showed apart from the effect of PNG content in soy, replacing animal protein with soy protein might have an additional adverse effect on B-6 status (Lu and Huang 1997). Based on the aforementioned evidence, the goal of our study was to determine the effect of substituting soymilk for cow's milk on vitamin B-6 status in middle aged women.…”
Section: Description Of the Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation